A novel ruthenium sensitizer with –OMe substituted phenyl-terpyridine ligand for dye sensitized solar cells. (September 2016) - Mongal, Binitendra Naath; Bhattacharya, Sayantani; Sengupta, Swaraj; Mandal, Tarun Kanti; Datta, Jayati; Naskar, Subhendu
Highlights: A novel, simple and cost effective polypyridyl based ruthenium photosensitizer for DSSCs. The efficiency of the dye is η = 4.62% under standard (AM 1.5) conditions at an optimized intensity of 50 mW cm −2 . The experimental absorption spectrum is well matched with calculated spectrum. Intense electronic transitions towards the dye-semiconductor interface probably due to the three(+R) –OMe groups. Abstract: A new ruthenium photosensitizer[Ru(triOMePhtpy)(bpydca)(NCS)]PF6 (1) (triOMePhtpy = 4′-(3, 4, 5-triOMe)Phenyl-2, 2′:6′, 2″-terpyridine;bpydca = 4, 4′-dicarboxy-2, 2′-bipyridine) has been synthesized and characterized by IR, UV–Vis, NMR and Mass spectroscopy. The molecule shows a moderately intense MLCT band at 511 nm. Along with the intraligand transitions in the UV region, the molecule shows several high energy MLCT bands which has been nicely manifested by the TDDFT calculation. DFT optimized structure shows a distorted octahedral geometry around central ruthenium atom, where the phenyl ring attached to the 4′ position of terpyridine moiety makes a torsion angle of 34.09° with the central pyridine ring. p K a of the –COOH functionalities was determined spectrophotometrically by monitoring the variation of MLCT band position with pH and found to be ∼3.98. Photovoltaic measurements of the present dye in a typical DSSC configuration was found to exhibit Jsc = 5.10 mA cm −2, FF = 66.02%, Voc = 0.68 V and η = 4.62% at an optimized intensity of 50 mW cm −2 .